Winning over the baker - Thorne, Danielle (Love inspired ;, 2025)
"Just when Tam Rochester's dreams of expanding her herb shop and being able to support her daughter are finally coming true, Patrick Butler arrives in town. She wasn't counting on the single dad's plans for a bakery right across the street or the competition it'll bring. Tam's not afraid to fight for her future, but going toe-to-toe with Patrick would be easier if she didn't adore his kids--and if she could just ignore her growing feelings for the too-talented baker..." --